Offers and offer refusals a postcolonial pragmatics perspective on world Englishes - Anchimbe, Eric A. (Pragmatics & beyond new series (P&bns),, 2018)
"This study offers a pragmatic dimension to World Englishes research. It is particularly timely because pragmatics has generally been understudied in past research on World Englishes, especially postcolonial Englishes. Apart from drawing attention to the paucity of research, the book also contributes to theory formation on the emerging theoretical framework, postcolonial pragmatics, which is then applied to data from two World (postcolonial) Englishes, Ghanaian and Cameroon Englishes. The copious examples used clearly illustrate how postcolonial societies realise various pragmatic phenomena, in this case offers and offer refusals, and how these could be fruitfully explained using an analytical framework designed on the complex internal set ups of these societies. For research on social interaction in these societies to be representative, it has to take into account the complex history of their evolution, contact with other systems during colonialism, and the heritages thereof. This book does just that"--